2004
DOI: 10.4049/jimmunol.173.5.3186
|View full text |Cite
|
Sign up to set email alerts
|

Folate Deficiency Inhibits the Proliferation of Primary Human CD8+ T Lymphocytes In Vitro

Abstract: Folate is required for one-carbon transfer reactions and the formation of purines and pyrimidines for DNA and RNA synthesis. Deficiency of folate can lead to many clinical abnormalities, including macrocytic anemia, cardiovascular diseases, birth defects, and carcinogenesis. The nucleotide imbalance due to folate deficiency causes cell cycle arrest in the S phase and uracil misincorporation into DNA, which may result in DNA double-strand breaks during repair. The role of folate in the immune system has not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(112 citation statements)
references
References 51 publications
(48 reference statements)
5
103
0
4
Order By: Relevance
“…There is some evidence that a deficiency or lack of folate intake significantly alters the immune response (Dhur et al, 1991;Courtemanche et al, 2004). Folate is related to lower concentrations of inflammatory markers and oxidative stress (Graham and O'Callaghan, 2000;Nanri et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that a deficiency or lack of folate intake significantly alters the immune response (Dhur et al, 1991;Courtemanche et al, 2004). Folate is related to lower concentrations of inflammatory markers and oxidative stress (Graham and O'Callaghan, 2000;Nanri et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Large quantities of dUTP may be incorporated instead of dTTP during S-phase (or DNA repair). The resulting A:U mismatches, however, do not result in mutations, but may hamper recognition by DNA-binding proteins and thus alter physiological function (Courtemanche et al, 2004). Levels of uracil in the DNA of UngϪ/Ϫ cells strongly depend on proliferation (Andersen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…One in vitro study revealed that the proliferative activity of primary human CD8-positive cytotoxic T-lymphocytes was inhibited by folate deficiency [21]. It has also been demonstrated in vitro that folate deficiency induces apoptotic cell death of phytohemagglutinin-stimulated human primary lymphocytes from the blood through triggering mitochondrial membrane depolarization [22].…”
Section: Discussionmentioning
confidence: 99%